The association between gallstone disease and plaque in the abdominopelvic arteries - Serin, Halil İbrahim (J Res Med Sci, 2017)
BACKGROUND: The aim of this study was to assess the atheromatous plaque, in the abdominopelvic arteries as a marker of cardiac risk in patients with or without gallstone disease (GD). MATERIALS AND METHODS: A total of 136 patients were enrolled in this cross-sectional study. Forty-eight patients had GD and the remaining 88 patients did not. The presence or absence of gallstones was noted during abdominal ultrasonography while vascular risk factors such as plaque formation, intima-media thickness, plaque calcification, mural thrombus, stenosis, aneurysm, and inflammation were recorded during an abdominopelvic computed tomography scan. In addition, percentage of the abdominopelvic aorta surface covered by atheromatous plaque was calculated. RESULTS: The mean age of patients with GD and without GD was 50.81 ± 16.20 and 50.40 ± 12.43, respectively. Patients with GD were more likely to have diabetes mellitus, a higher body mass index (BMI) (P < 0.001), and higher cholesterol (P < 0.01), and low-density lipoprotein-cholesterol (P < 0.02) levels. No significant differences were found between the groups regarding other atherosclerotic risk factors. Patients with GD had significantly higher rates of the vascular risk factors as intima-media thickness, plaque formation, calcification, aneurysm, mural thrombosis, stenosis, and inflammation in all abdominal arterial segments other than aneurysm in the femoral arteries. In addition, patients with GD had severe atheromatous plaques in the abdominal aorta, common iliac, external iliac, and common femoral artery (CFA). In patients with GD, parameters of age, BMI, and systolic and diastolic blood pressure were all correlated with the severity of the atheromatous plaque in abdominal aorta, common iliac, external iliac, and CFA. CONCLUSION: We demonstrated a direct relationship between GD and abdominopelvic atheromatous plaque, which is a marker for increased cardiovascular risk, for the first time in the literature. Patients with GD exhibit greater abdominopelvic atherosclerosis and therefore, have a higher risk of cardiovascular disease.